A comparative analysis of transfer pricing regulation in Indonesia and Malaysia - Irawan, Ferry; Taha, Roshaiza (WIM Solusi Prima, 2025)
Transfer pricing (TP) regulation has become a central feature of tax administration in Southeast Asia as jurisdictions intensify compliance frameworks aligned with global anti–base erosion standards. This article presents a doctrinal and comparative legal analysis of Indonesia’s transfer pricing regime under Minister of Finance Regulation No. 172 of 2023 (PMK 172/2023) and Malaysia’s Transfer Pricing Guidelines 2024 (TPG 2024). Drawing on primary legal and administrative sources, the study compares the two systems across key dimensions, including regulatory foundations, the definition of associated parties, the application of the arm’s length principle, transfer pricing methods, the treatment of specific controlled transactions, contemporaneous documentation requirements, and dispute-prevention and resolution mechanisms. The analysis identifies substantial convergence in the conceptual design of the arm’s length principle and the methodological tools adopted in both jurisdictions. However, significant divergence remains in compliance architecture and enforcement strategy. Indonesia emphasizes a staged approach to arm’s length testing supported by tiered documentation and integration with annual tax return filings, while Malaysia adopts a threshold-based documentation model with strict furnishing timelines and explicit offence provisions. The article concludes by outlining practical compliance implications for multinational enterprises and discussing broader policy considerations for tax certainty and transfer pricing dispute risk management in the region.